Recycling paper - Condon, Judith (New York : F. Watts, 1990)
Discusses the problems caused by the manufacture and disposal of paper products, and proposes methods for recycling them to reduce such threats.
Includes index.
Booklist.
School Library Journal.
6.9
6.9
3-6.
Keywords: Paper industry -- Environmental aspects -- Juvenile literature; Waste paper -- Recycling -- Juvenile literature; Paper industry -- Environmental aspects; Recycling (Waste); Waste paper -- Recycling; Paper industry -- Environmental aspects; Recycling; Waste products